Fibrinogen-to-albumin ratio is related to the severity of coronary artery disease in chronic kidney disease patients undergoing coronary angiography - Li-Hua Lin; Hong Liu; Dong-Hua Jin; Jun Zou; Yu-Xian Xie; Hong Qiu; Miao Jia; Da-Mei Li; Bi-Cheng Liu (Nefrología (English Edition), 2022)
Objectives: This study was to explore the potential relationship between the fibrinogen-to-albumin ratio (FAR) and the presence and severity of coronary artery disease (CAD) in stage 3–5 predialysis chronic kidney disease (CKD) patients. Design: This study included 978 patients undergoing coronary angiography (CAG). CAD was defined as the presence of obstructive stenosis > 50% of the lumen diameter in any of the four main coronary arteries. Gensini scores (GSs), left main coronary artery (LMCA) and three-vessel coronary artery disease (TVD) were used to elevate the severity of CAD. Results: The adjusted odds ratios of CAD were 3.059 (95% CI: 1.859–5.032) and 2.670 (95% CI: 1.605–4.441) in the third and fourth quartiles of FAR compared with the first quartile, respectively. Among 759 patients diagnosed with CAD, multivariate logistic regression analysis showed that FAR (at the 0.01 level) was significantly positively associated with the presence of LMCA (adjusted OR = 1.177, 95% CI 1.067–1.299, P = 0.001) or TVD (adjusted OR = 1.154, 95% CI 1.076–1.238, P < 0.001), and a higher GS (adjusted OR = 1.152, 95% CI 1.073–1.238, P < 0.001). Conclusions: FAR levels were independently associated with the presence and severity of CAD in stage 3–5 predialysis CKD patients. Resumen: Objetivos: Este estudio pretendía explorar la relación potencial entre la relación fibrinógeno/albúmina (FAR) y la presencia y la gravedad de la enfermedad arterial coronaria (EAC) en pacientes con enfermedad renal crónica (ERC) en estadio 3-5 en la etapa prediálisis. Diseño: Este estudio incluyó a 978 pacientes tratados mediante angiografía coronaria. La EAC se definió como la presencia de estenosis obstructiva > 50% del diámetro de la luz de cualquiera de las 4 arterias coronarias principales. Se utilizaron las puntuaciones de Gensini (GS), la enfermedad de la arteria coronaria izquierda (EACI) y la EAC de 3 vasos (ETV) para evaluar la gravedad de la EAC. Resultados: Los cocientes de posibilidades de EAC fueron 3,059 (IC del 95%: 1,859-5,032) y 2,670 (IC del 95%: 1,605-4,441) en el tercer y el cuarto cuartiles de la FAR en comparación con el primer cuartil, respectivamente. Entre los 759 pacientes diagnosticados de EAC, el análisis de regresión logística de múltiples variables mostró que la FAR (al nivel 0,01) presentaba una asociación positiva significativa con la presencia de EACI (OR ajustada = 1,177, IC del 95%: 1,067-1,299, p = 0,001) o ETV (OR ajustada=1,154, IC del 95%: 1,076-1,238, p < 0,001) y una puntuación GS mayor (OR ajustada = 1,152, IC del 95%: 1,073-1,238, p < 0,001). Conclusiones: Los niveles de FAR se asociaron de manera independiente con la presencia y la gravedad de EAC en los pacientes con ERC en estadio 3-5 en la etapa prediálisis.